2014
DOI: 10.1016/j.jbiosc.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Control of adhesion of human induced pluripotent stem cells to plasma-patterned polydimethylsiloxane coated with vitronectin and γ-globulin

Abstract: Human induced pluripotent stem cells (hiPSCs) are a promising source of cells for medical applications. Recently, the development of polydimethylsiloxane (PDMS) microdevices to control the microenvironment of hiPSCs has been extensively studied. PDMS surfaces are often treated with low-pressure air plasma to facilitate protein adsorption and cell adhesion. However, undefined molecules present in the serum and extracellular matrix used to culture cells complicate the study of cell adhesion. Here, we studied the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Figure 5(b) is followed by the functionalization of the surface with γ-globulin and vitronectin and the interactions with human-induced pluripotent cells (hiPSCs). It was found that γ-globulin on the untreated PDMS surfaces blocked the vitronectin adsorption, which prevents hiPSC adhesion [177]. It was reported that allylamine plasma deposition on poly(D,L-lactic acid) (PDLLA) promoted N3T3 fibroblast adhesion and proliferation.…”
Section: Biomedical Polymeric Substratesmentioning
confidence: 99%
“…Figure 5(b) is followed by the functionalization of the surface with γ-globulin and vitronectin and the interactions with human-induced pluripotent cells (hiPSCs). It was found that γ-globulin on the untreated PDMS surfaces blocked the vitronectin adsorption, which prevents hiPSC adhesion [177]. It was reported that allylamine plasma deposition on poly(D,L-lactic acid) (PDLLA) promoted N3T3 fibroblast adhesion and proliferation.…”
Section: Biomedical Polymeric Substratesmentioning
confidence: 99%
“…More recently, new reagents such as small molecules which target specific intracellular pathways have been proposed for stem cell differentiation protocols, and are now widely used in a soluble form in culture media (Xu et al, ). At the same time, studies have focused on immobilization or pre‐coating bioactive signals on cell culture substrates or the surface of implantable scaffolds (Bacakova et al, ; Chen et al, ; Chuah et al, ; Duffy et al, ; Kang et al, ; Kuddannaya et al, ; Lu et al, ; Nagaoka et al, ; Yamada et al, ). This has the potential to establish more defined culture systems and be used in future clinical applications, such as commercialized cell culture tools (Higuchi et al, ; Wang et al, ) and tissue engineered implants (Salerno et al, ).…”
Section: Biochemical Stimulationmentioning
confidence: 99%
“…Direct surface modification is another method that has been used to influence cell behavior. Protein coatings, such as Type I collagen (Chuah et al, 2015;Kuddannaya et al, 2013) or fibronectin (Kuddannaya et al, 2013;Wang et al, 2012e;Yamada et al, 2014), can be applied to facilitate attachment of MSCs and iPSCs to hydrophobic surfaces like polydimethylsiloxane (PDMS). Different surface properties provided by these modifications can affect the density and configuration of protein adsorption prior to cell culture or from media, which in turn affects cell adhesion and growth (De Luca et al, 2015).…”
Section: Surface-immobilized Biosignalsmentioning
confidence: 99%
“…The patterning of cells, including hiPSCs, can be easily performed by masked plasma oxidation, which uses patterned physical masks to partially prevent plasma treatment. [7][8][9][10] Using masked plasma oxidation, we succeeded in creating hiPSC patterns (2-mm-diameter discs) on polydimethylsiloxane (PDMS) surfaces under culture conditions defined in a previous study. 9 PDMS is one of the most popular biocompatible materials for research and development of small cell culture devices because this elastomer is nontoxic, chemically inert, transparent, and gas permeable.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Using masked plasma oxidation, we succeeded in creating hiPSC patterns (2-mm-diameter discs) on polydimethylsiloxane (PDMS) surfaces under culture conditions defined in a previous study. 9 PDMS is one of the most popular biocompatible materials for research and development of small cell culture devices because this elastomer is nontoxic, chemically inert, transparent, and gas permeable. [11][12][13] Plasma treatment on PDMS oxidized ≡Si-CH 3 to generate ≡Si-O-Si≡ groups suggests that hydrophilic and siliceous layers were formed on the surface 9,11 (Fig.…”
Section: Introductionmentioning
confidence: 99%